(Information letter) A treatment method for Covid-19 infection in patients with inflammatory joint diseases - Martynov, Artur; Grishyna, Olena; Menkus, Olena (Annals of Mechnikov's Institute, 2023)
The implementation involved a new method of treating COVID-19 infection in patients with inflammatory joint diseases. The method includes the addition of sulodexide to standard therapy in outpatient settings. An open randomized controlled trial was conducted with 53 patients suffering from inflammatory joint diseases. The patients were divided into two groups; group 1 received sulodexide in addition to standard therapy for COVID-19 while group 2 received only standard therapy. The results showed that supplementing the standard therapy of COVID-19 with sulodexide in patients with inflammatory joint diseases led to a reduction in clinical symptoms such as shortness of breath, palpitations, cardiac pain, fatigue, and also helped to normalize laboratory indicators - markers of inflammation (interleukin-6, C-reactive protein, D-dimer). Keywords: Covid-19, inflammatory joint diseases, treatment